Beyond Safety Training: Embedding Safety in Professional Skills - Bieder, Corinne; Gilbert, Claude; Journé, Benoît; Laroche, Hervé (SpringerBriefs in Safety Management, 2017)
FonCSI; professionalization of safety; risk management